Kedudukan Hukum Pemegang Hak Preferen dan Retensi terhadap Perusahaan PT Bukit Inn Resort yang Dinyatakan Pailit - I Putu Angga Septayana; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Interpretasi Hukum, 2022)
Entrepreneurs have a strategy so that their business is always in a stable condition, namely by borrowing additional funds from third parties. Especially in Bali, entrepreneurs can seek additional funds through financial institutions/LPDs (Village Credit Institutions). However, many companies were declared bankrupt because they did not fulfill their obligations. This study aims to examine the legal position of the holder of preference rights and retention of the company PT. Bukit INN Resort which was declared bankrupt. The method used in this study is the normative legal method with a statutory, conceptual and case approach. This study uses primary and secondary data. Analysis of the data used is a qualitative analysis. The results showed that the settlement of preference rights and retention rights for the curator of the company PT. Bukit INN Resort is carried out in accordance with the provisions of Article 15 paragraph (1) of Law no. 37 of 2004. Legal efforts are carried out by the parties concerned who must explicitly do so in order to obtain a solution or settlement of the legal problems they face, after taking legal action, the parties concerned will obtain a judge's decision that has legal force.